Pengujian Kuat Tekan dan Kuat Tarik Belah Beton Dengan Bahan Tambah Limbah Polyvinyl Chloride (PVC) - Tri Yogi Wibowo; Eko Walujodjati (Institut Teknologi Garut, 2025)
PVC is a thermoplastic polymer that ranks third in global usage, after polyethylene and polypropylene. Polyvinyl Chloride (PVC) is one of the most difficult types of plastic to recycle. Utilizing this waste efficiently presents a significant challenge; however, if PVC waste can be technically proven suitable as a material or aggregate in concrete mixtures, it could help reduce environmental pollution. The purpose of this study is to examine the effect of PVC waste as an additive on the compressive and splitting tensile strength of concrete. The research was carried out experimentally in a laboratory setting, using three variations of concrete mixtures: normal concrete, concrete with 3% PVC, and concrete with 6% PVC, based on the weight of the coarse aggregate. A total of 18 samples were prepared, with a planned concrete strength of fc’ = 20 MPa. Concrete testing was performed at 28 days of curing, referring to the Indonesian National Standard SNI-03-1974-2011. The results showed that the average compressive strength values were 11.31 MPa for normal concrete, 13.58 MPa for concrete with 3% PVC, and 16.59 MPa for concrete with 6% PVC. In contrast, the average splitting tensile strength values were 4.29 MPa for normal concrete, 3.70 MPa for concrete with 3% PVC, and 3.11 MPa for concrete with 6% PVC. These findings indicate that the addition of PVC waste improves compressive strength but reduces tensile strength, suggesting that while PVC waste can enhance certain structural properties, it does not meet the requirements for tensile reinforcement in concrete mixtures.